2015
DOI: 10.1080/19476337.2015.1020342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of probiotic potential of lactic acid bacteria isolated from traditional Malaysian fermentedBambangan(Mangifera pajang)

Abstract: Evaluation of probiotic potential of lactic acid bacteria isolated from traditional Malaysian fermented Bambangan (Mangifera pajang)Evaluación del potencial probiótico de bacterias acido-lácticas aisladas del tradicional Bambangan malasio fermentado (Mangifera pajang) This study aims to evaluate the probiotic and technological properties of lactic acid bacteria (LAB) isolated from an indigenous fermentation of Bambangan (Mangifera pajang). The LAB were evaluated for their tolerance to low pH, bile salt, antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 53 publications
6
28
0
3
Order By: Relevance
“…Although other strains showed a relatively lower viable count, the count of these strains was still higher than the ATCC 8014 reference strain. These results are in line with those reported by Ng, Koon, Padam, and Chye (2015), who found that when the pH is reduced to 1.8 simulating the last gastric emptying to the intestine, a drastic reduction of the viability takes place. Eriksen et al (2010) indicated that the actual pH of the stomach is 3.0 during food ingestion, because food ingestion has a buffering effect which raises the pH level to 3.0, whereas the pH of the stomach when fasted can be as low as pH 2.0.…”
Section: Gastrointestinal Transit Tolerancesupporting
confidence: 93%
See 1 more Smart Citation
“…Although other strains showed a relatively lower viable count, the count of these strains was still higher than the ATCC 8014 reference strain. These results are in line with those reported by Ng, Koon, Padam, and Chye (2015), who found that when the pH is reduced to 1.8 simulating the last gastric emptying to the intestine, a drastic reduction of the viability takes place. Eriksen et al (2010) indicated that the actual pH of the stomach is 3.0 during food ingestion, because food ingestion has a buffering effect which raises the pH level to 3.0, whereas the pH of the stomach when fasted can be as low as pH 2.0.…”
Section: Gastrointestinal Transit Tolerancesupporting
confidence: 93%
“…Lactobacillus strains TAP1, BU14, and TEMP9 exhibited excellent capabilities to inhibit indicator pathogenic bacteria and are considered better than the reference strain ATCC 8014, and more like the commercial strain ATCC5103. Different levels of inhibitory activities were reported for some other lactobacilli isolated from various sources (Hor & Liong, 2014;Ng et al, 2015;Ramos et al, 2013;Roberts et al, 1995). The prior study by Cruz-Guerrero et al (2014) highlighted that SCFA, H 2 O 2, and bacteriocins are among the main reported Table 3.…”
Section: Antibacterial Activity Testsmentioning
confidence: 99%
“…The survivability of L. plantarum LRCC5193 in acidic condition was maintained at 99 log percentage, whereas the survivability in bile condition also remained high at 98.6 log percentage. This data was in agreement with Ng, Koon, Padam, and Chye (), where plant‐isolated L. plantarum strains are capable of regulating internal pH and thereby exhibiting higher survivability at pH 3.0 compared to the other Lactobacillus sp. Additionally, L. plantarum strains isolated from fermented vegetables have been well documented for their potential probiotic functional properties (Behera, Ray, & Zdolec, ).…”
Section: Resultssupporting
confidence: 92%
“…Five out of twenty lactobacilli isolates showing highest resistance towards acid, bile and lysozyme were selected for further probiotic characterization. The behavior of LAB cells in gastrointestinal fluids was evaluated following the method described by Ng et al (2015). Resistance in terms of total viable count was determined after 3 h in simulated gastric fluid (SGF) and 4 h in simulated intestinal fluid (SIF).…”
Section: Evaluation In Gastrointestinal Fluidsmentioning
confidence: 99%
“…Most of the commercial and widely used probiotic bacteria belong to genera Lactobacillus and Bifidobacterium. Probiotic bacteria have several desirable characteristics such as resistance against acid and bile salts, tolerance to gastrointestinal tract conditions, antimicrobial activity against pathogens, capability to adhere and colonize intestinal cell wall and absence of unusual antibiotic resistance (Ng et al, 2015). Probiotics maintain microbial balance in intestine, prevent and inhibit the growth of pathogenic bacteria and cure various intestinal diseases.…”
Section: Introductionmentioning
confidence: 99%